Teacher Strategies in Improving Elementary School Students’ Critical Thinking Skills by Using The Giving Question and Getting Answer Learning Model - Sahat T. Simorangkir; Isthifa Kemal; Reza Rachmatullah; Eddy Setyanto (Postgraduate, University of Mataram, 2025)
This ability is not only important for academic success, but also essential for students to face complex problems in everyday life. This study aims to examine the effectiveness of the Giving Question and Getting Answer model in improving students' critical thinking skills. The research design used a posttest-only control group design experiment. The research instrument was a critical thinking ability test that included the dimensions of analysis, evaluation, and problem solving. Data were analyzed using a t-test to compare the average posttest results of the two groups. The results of this study are that the use of the Giving Question and Getting Answer (GQGA) model has proven effective in improving students' critical thinking skills. The GQGA model is suitable for implementation at the elementary school level because it is in accordance with the needs of students to learn through interactions involving cognitive and social aspects. With the right approach, this model is able to overcome the limitations of traditional learning methods that do not support the development of students' critical thinking skills.